2013
DOI: 10.1111/1475-6773.12076
|View full text |Cite
|
Sign up to set email alerts
|

Plan–Provider Integration, Premiums, and Quality in the Medicare Advantage Market

Abstract: Objective. To investigate how integration between Medicare Advantage plans and health care providers is related to plan premiums and quality ratings. Data Source. We used public data from the Centers for Medicare and Medicaid Services (CMS) and the Area Resource File and private data from one large insurer. Premiums and quality ratings are from 2009 CMS administrative files and some control variables are historical. Study Design. We estimated ordinary least-squares models for premiums and plan quality ratings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 24 publications
7
31
0
Order By: Relevance
“…In line with prior literature in this area, the premium analyses show that plans that tend to operate in more concentrated MA markets are associated with higher premiums as compared to those that tend to operate in competitive MA markets. However, the impact of insurer market concentration on premiums may be modified by MA plan quality.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In line with prior literature in this area, the premium analyses show that plans that tend to operate in more concentrated MA markets are associated with higher premiums as compared to those that tend to operate in competitive MA markets. However, the impact of insurer market concentration on premiums may be modified by MA plan quality.…”
Section: Discussionsupporting
confidence: 82%
“…In line with prior literature in this area, 16 modify benefit packages more frequently than contract mergers occur. However, enrollment-weighted contract-level quality ratings data obscure any differences in quality at the individual plan level, making it difficult to know whether a high-quality rating reflects high performance across all plans within a contract, or whether there is variable performance across plans.…”
Section: Ta B L Esupporting
confidence: 76%
See 1 more Smart Citation
“…In a 2013 study, Frakt and colleagues found that provider-offered contracts had higher CMS star ratings than other contracts, and these provider-offered contracts also had higher premiums, even when controlling for quality 3. Similarly, in 2017 Johnson et al found that provider-offered MA contracts have higher overall CMS star ratings than others, and also significantly outperform other contracts in domain-level star ratings 4.…”
Section: Discussionmentioning
confidence: 97%
“…Early evidence is encouraging that ACOs can improve quality without increasing costs to Medicare (Gold 2013). However, the implications of ACOs and the consolidation they encourage on private prices have not yet been directly assessed (Frakt, Pizer, and Feldman 2013).…”
Section: Cutting Fat or Muscle?mentioning
confidence: 99%